Social, Cultural, and Economic Factors Affecting Recidivism: Perspectives of Workers in Correctional and Penal Institutions - Albashkardi, Fatema; Hamdi, Wafa (Al-Adab Journal, 2025)
The current study sought to reveal the impact of social, cultural and economic factors on recidivism from the perspective of workers in penal and correctional centers in the United Arab Emirates. Therefore, the research followed the descriptive analytical approach by preparing a questionnaire consisting of two sections: the primary data section, and the influential factors section, which includes three axes: social factors - economic factors - cultural factors. The questionnaire was applied to 30 male and female workers in the UAE correctional and punishment centers. The results of the study revealed that social factors have a high impact on recidivism with an average of (3.526) and a percentage of (70.7%), while economic factors had a medium impact on recidivism with an average of (3.44) and a percentage of (68.8%), and cultural factors had a high impact on recidivism with an average of (3.50) and a percentage of (70.1%), while the contribution of these factors combined was (16.2%) in recidivism from the sample's point of view.